Analysis of the truncated response model for fixed priority on HMPSoCs - Brandão, Jesse Wayde (2015)
With the ever more ubiquitous nature of embedded systems and their increasingly demanding applications, such as audio/video decoding and networking, the popularity of MultiProcessor Systems-on-Chip (MPSoCs) continues to increase. As such, their modern uses often involve the execution of multiple applications on the same system. Embedded systems often have applications that are faced with timing restrictions, some of which are deadlines, throughput and latency. The resources available to the applications running on these systems are nite and, therefore, applications need to share the available resources while guaranteeing that their timing requirements are met. These guarantees are established via schedulers which may employ some of the many techniques devised for the arbitration of resource usage among applications. The main technique considered in this dissertation is the Preemptive Fixed Priority (PFP) scheduling technique. Also, there is a growing trend in the usage of the data ow computational model for analysis of applications on MultiProcessor System-on-Chips (MPSoCs). Data ow graphs are functionally intuitive, and have interesting and useful analytical properties. This dissertation intends to further previous work done in temporal analysis of PFP scheduling of Real-Time applications on MPSoCs by implementing the truncated response model for PFP scheduling and analyzing the its results. This response model promises tighter bounds for the worst case response times of the actors in a low priority data ow graph by considering the worst case response times over consecutive rings of an actor rather than just a single ring. As a follow up to this work, we also introduce in this dissertation a burst analysis technique for actors in a data ow graph.